REVEALING LISTENING COMPREHENSION DIFFICULTIES AND STRATEGIES ENCOUNTERED BY HIGH ACHIEVERS OF THE FOURTH SEMESTER ENGLISH DEPARTMENT STUDENTS - Virnanda Igo Rahmadana; Yahya Alaydrus; Nuse Aliyah Rahmati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
The objectives of this study were to reveal students’ listening comprehension difficulties and strategies to overcome the listening comprehension problems by high achievers. The strategies were necessary to improve the listening skill and counter the difficulties in listening comprehension. The research method was qualitative research method. The participants of this study were four students. The researcher was asked for recommendation to the listening lecturers, then the researcher met them personally, then the researcher conducted the open-ended interview session to collect the data. The researcher was used familiarizing and organizing, coding and reducing, and interpreting and organizing to analyze the collected data. The findings of the research explained that the difficulties included limited vocabulary, speed of native speakers’ speech, natives speakers’ accent, classroom environment, lack of concentration and motivation. However, the students’ strategies were the use of media as the learning tool, practicing listening material continuously and reading short stories to get new vocabulary. The students suggested applying the strategies provided to overcome their difficulties. However, this research was expected to be developed by the future researchers who had the same interest.